Sürdürülebilir ulaşımda bisikletin önemi ve Gebze Teknik Üniversitesinde bisiklet alanı konumlandırılması - Erben, Burcu (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2019)
Son yıllarda insan sayısı gözle görünür şekilde artmış durumdadır. Bu, şehir alanlarında ulaşım ihtiyacını yaratmaktadır. Çünkü, kentsel genişleme ile birlikte çok sayıda ulaşım türleri kullanılmaktadır. Ulaşım türlerinin fazla sayısıda olması trafik sıkışıklığı, alan yetersizliği gibi birçok soruna neden olmaktadır. Bu sebeple şehir alanlarında düzenleme ve kullanım avantajı konusuna yönelimde daha titiz davranılmalıdır. Bu yüzden sürdürülebilir yapılandırma insanlar için önemli bir rol oynamaktadır. Bunun yanı sıra, ulaşım ihtiyacı insanları diğerlerinden ucuz ulaşım türleri aramaya yönlendiriyor. Sürdürülebilir ulaşım için bisiklet avantajlı görünebilir. Gebze Teknik Üniversitesi öğrencilerinin birçok avantajı vardır. Üniversite öğrencileri çok sayıda bisiklete kolayca erişim sağlayabilir. Bisiklet onların ulaşım ihtiyaçlarını karşılamaktadır. Bu çalışmada hem sürdürülebilirliğe katkı sağlamak hem de Gebze Teknik Üniversitesi içinde bisiklet istasyonlarının Gams programı yoluyla belirlenmesi amaçlanmıştır. Elde edilen sonuca göre bulunan noktalar 3 farklı alandadır.

The number of people has increased noticeably over last years. İt creates a need for transportation in urban areas. Because, with the improvements in urban expansion a great deal of transportation modes has been used. The need for more transportation leads people to seek cheaper than others. A large number of transport types causes many problems such as traffic jam, insufficient area. For this reason, it should be more meticulous in the orientation towards the advantage of regulation and usage in urban areas. Therefore, Sustainable structuring plays a very significant role for people. Besides, the need for transportation directs people to seek cheaper modes of transport from others. The bike can appear advantageous for sustainable transportation. There are many advantages to Gebze Technical University students. University students have easy access to a large number of bikes. Bike satisfies their transport needs. In this study, it is aimed to contribute to the sustainability and to determine the bicycle stations in Gebze Technical University through Gams program. According to the result, founded points are in 3 different areas.
The importance of bike in sustainable transportation and location of the bicycle area at Gebze Technical University
Keywords: Ulaşım; Transportation; İşletme